Mediastinal dermoid cyst with rupture in the pericardium - Prashant Mishra; Noaman Shaikh; Chaitanya Raut (Termedia Publishing House, 2022)
Extragonadal germ cell tumours are rare neoplasms constituting 3-4% of all germ cell tumours and less than 1% of all tumours [1]. The mediastinum is the most common site for extragonadal germ cell tumours. Teratomas are the most common mediastinal germ cell tumours. Mature cystic teratoma is commonly known as dermoid cyst [2]. Cystic teratomas are mostly asymptomatic and are detected incidentally. However, they can present with clinical features of rupture in the adjacent areas such as the pleura, pericardium, lung or bronchus [2].